On the meaning and measurement of maximization - Cheek, Nathan N.; Schwartz, Barry (Judgment and Decision Making, 2016)
Building on Herbert Simon’s critique of rational choice theory, Schwartz et al. (2002) proposed that when making choices, some individuals — maximizers — search extensively through many alternatives with the goal of making the best choice, whereas others — satisficers — search only until they identify an option that meets their standards, which they then choose. They developed the Maximization Scale (MS) to measure individual differences in maximization, and a substantial amount of research has now examined maximization using the MS, painting a picture of maximizers that is generally negative. Recently, however, several researchers have criticized the MS, and almost a dozen new measures of maximization have now been published, resulting in a befuddling and contradictory literature. We seek to clarify the confusing literature on the measurement of maximization to help make sense of the existing findings and to facilitate future research. We begin by briefly summarizing the understanding of maximizers that has emerged through research using Schwartz et al.’s MS. We then review the literature on the measurement of maximization, attempting to identify the similarities and differences among the 11 published measures of maximization. Next, we propose a two-component model of maximization, outlining our view of how maximization should be conceptualized and measured. Our model posits that maximization is best understood as the pursuit of the maximization goal of choosing the best option through the maximization strategy of alternative search; other constructs such as decision difficulty and regret are best considered outcomes or causes — rather than components — of maximization. We discuss the implications of our review and model for research on maximization, highlighting what we see as pressing unanswered questions and important directions for future investigations.